Effects of corticosteroids and immunosuppressors on idiopathic inflammatory myopathy related myocarditis evaluated by magnetic resonance imaging. Issue 2 (12th January 2006) - Allanore, Y; Vignaux, O; Arnaud, L; Puéchal, X; Pavy, S; Duboc, D; Legmann, P; Kahan, A
Abstract : Background: Cardiac involvement in idiopathic inflammatory myopathy has been recognised as an important prognostic factor, but treatment remains empirical. Objective: To investigate the effects of corticosteroids and immunosuppressors on myocarditis in patients with inflammatory myopathies. Methods: Patients with inflammatory myositis of recent onset who had not received treatment were evaluated for associated myocarditis by magnetic resonance imaging (MRI) and reinvestigated after treatment with high dose corticosteroids and immunosuppressors. Results: Four patients with histologically proven myositis were included. Two patients with polymyositis had cardiac clinical symptoms. Two other patients with dermatomyositis and diffuse cutaneous systemic sclerosis-polymyositis overlap syndrome were asymptomatic. In three cases the usual conventional screening tests were normal. For all patients an area of contrast enhancement and hypokinesia detected by cardiac MRI was markedly reduced after treatment with corticosteroids and immunosuppressors for 6 months. Conclusion: Treatment with intravenous methylprednisolone followed by prednisone and immunosuppressive therapy seems to be effective for treating myocardial involvement in patients with idiopathic inflammatory myopathies, either alone or presenting as overlap syndromes. Cardiovascular MRI is a non-invasive technique that may be a powerful tool for diagnosis and monitoring of myocardial inflammation in this setting.